2004
DOI: 10.1128/jcm.42.4.1739-1741.2004
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymorphism Assay Distinguishes Isolates ofLeishmania donovaniThat Cause Kala-Azar from Those That Cause Post-Kala-Azar Dermal Leishmaniasis in Humans

Abstract: Leishmania donovani in India causes visceral infection (kala-azar) and dermal infection (post-kala-azar dermal leishmaniasis). We report here the identification of polymorphism in a well-defined genetic locus among the Leishmania parasites causing the visceral and dermal manifestations, in a comparison of 15 post-kala-azar dermal leishmaniasis and 12 kala-azar patient isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
(19 reference statements)
2
21
0
2
Order By: Relevance
“…An informed consent based on the guidelines of the Ethical Committee, Safdarjung Hospital, New Delhi, was obtained from the patients. L. donovani isolates were prepared from bone marrow aspirates of VL patients, as described elsewhere (Sreenivas et al 2004a). All the isolates were characterised as L. donovani, on the basis of reaction with species-specific monoclonal antibody and/ or polymerase chain reaction (Sreenivas et al 2004b).…”
Section: Methodsmentioning
confidence: 99%
“…An informed consent based on the guidelines of the Ethical Committee, Safdarjung Hospital, New Delhi, was obtained from the patients. L. donovani isolates were prepared from bone marrow aspirates of VL patients, as described elsewhere (Sreenivas et al 2004a). All the isolates were characterised as L. donovani, on the basis of reaction with species-specific monoclonal antibody and/ or polymerase chain reaction (Sreenivas et al 2004b).…”
Section: Methodsmentioning
confidence: 99%
“…Such parasite strains may be differentiated by the use of genetic tags [54,55]. Recent developments have even indicated that some genes are significantly overexpressed among isolates from patients with PKDL compared with those obtained from cases of visceral leishmaniasis [56].…”
Section: Parasite Strains As Determinants Of Clinical and Therapeuticmentioning
confidence: 99%
“…Studies of molecular DNA markers of parasites from mucosal lesions of leishmaniasis and from blood samples of patients with kalaazar have shown they represent different strains of L. donovani 13 . A similar study of genetic polymorphisms distinguishes L. donovani strain responsible for kala-azar from that in PKDL 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, keeping similarity to reports of different strains of L. donovani responsible for cutaneous and mucosal lesions in patients from Sudan and India 13,21 , genetic studies of strains of L. (L.) chagasi that affect the skin could be interesting to distinguish them of those that only affect internal organs in VL, mainly for the possibility of prediction of mucosal compromising. In this report it was possible to show similarity, using enzymatic digestion with HaeIII, of a 120 bp DNA fragment amplified from skin lesion from this patient with aids-VL co-infection and from blood sample collected from another patient with VL.…”
Section: Discussionmentioning
confidence: 99%